A spatial feature analysis of primary health care utilization in a large city in China and its implications for family doctor contract service policy - Xin Rao; Li Luo; Xingyue Wang (BMC, 2024)
Abstract Background Family doctor contract policy is now run by the State Council as an important move to promote the hierarchical medical system. Whether the family doctor contract policy achieves the initial government's goal should be measured further from the perspective of patient visits between hospitals and community health centers, which are regarded as grass medical agencies. Methods The spatial feature measurement method is applied with ArcGIS 10.2 software to analyze the spatial aggregation effect of patient visits to hospitals or community health centers among 20 districts of one large city in China and analyze the family doctor contract policy published in those areas to compare the influence of visit tendencies. Results From year 2016-2020, visits to hospitals were in the high-high cluster, and the density was spatially overflow, while there was no such tendency in visits to community health centers. The analysis of different family doctor contract policy implementation times in 20 districts reflects that the family doctor contract policy has a very limited effect on the promotion of the hierarchical medical system, and the innovation of the family doctor contract policy needs to be considered. Conclusions A brief summary and potential implications. A multi-integrated medical system along with family doctor contract policy needs to be established, especially integrated in leadership and governance, financing, workforce, and service delivery between hospitals and community health centers, to promote the hierarchical medical system.